Pengaruh Promosi di Media Sosial dan Harga Tiket Terhadap Minat Beli Pengguna Jasa Maskapai Citilink di Bandar Udara Internasional EL Tari Kupang - krisdayanti; Fryda Fatmayati (PT FORMOSA CENDEKIA GLOBAL, 2022)
PT. Citilink is one of the airlines that applies the LCC concept. Flights that provide cheap ticket prices and minimalist flight services are called LCC. This LCC-based airline offers an increase in the use of flight services in Indonesia. In addition , rivalry is also increasing due to the emergence of many airlines that are included in the category of low cost carriers. An effort that is needed to be able to compete and increase Citilink's sales volume is a promotional strategy and prices that are in line with the purchasing power of the market share. This study intends to partially test the effect of promotion on buying interest, partially test the effect of price on buying interest, test the effect of promotion and price simultaneously on buying interest. This research uses quantitative research. Methods of data collection by distributing questionnaires and documentation. The population in this study are Citilink airline service users at El Tari Kupang International Airport. The sampling technique used by the researcher is a non-probability sampling technique and purposive sampling with 100 users of Citilink airline services.Furthermore, the data analysis used is multiple analysis, T-test, F-test, coefficient of determination with the SPSS 20The results of this study state that promotions do not affect the buying interest of Citilink airline service users, there is a price effect on Citilink airline service users' buying interest, promotions and prices simultaneously affect the buying interest of Citilink airline service users. Promotion and price factors have an effect of 74.2 on buying interest on Citilink airlines, and the remaining 25.8% are influenced by other factors or other variables that are not known or not included in this study.